(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This essay tries to think about the historiographical making from its sensitive relationship with the world. It starts from the thought of the philosopher Walter Benjamin to question the superiority of the view over the other senses of the body in the ways of narrating the social. It seeks to think about a new relation of historiographical writing with these same meanings, understanding the gaze as a historical construction of a given time and a given society. Finally, it brings notes of an ongoing research on the discursive elaboration of a sound for the Northeast region, thus articulating time, space and sound.